Grazing impacts on savanna vegetation states and its role in albedo changes - Fernandes, Joana (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2018)
Albedo, i.e., the fraction of the incoming sunlight that a surface reflects, has been previously shown to play a key role on the climate system by influencing the energy balance of the Earth’s ecosystems. Shifts in land cover, such as deforestation for agriculture, or the creation of grazing lawns by grazers, are likely to alter albedo, which, in turn, can influence the local climate - higher albedos are associated with a net cooling effect, while lower albedos can lead to surface temperature increases. Raises in temperature have been previously linked to woody encroachment, process that can further lead to a warmer effect due to the reduced albedo of woody plants in comparison with grass. In the present study, I investigated how albedo differed between three distinct savanna vegetation types: grazing lawns, tall bunch grassland and woody encroached tall grassland. I showed that grazing lawns have a significantly higher albedo than woody encroached tall grass. Albedo decreased with the amount of bare soil, and increased with the amount of grass. However, it was not affected by woody cover. I also investigated the likelihood of shrub encroachment to happen in lawns and tall bunch grass, and found that it happens more easily in tall bunch grass. This study supports that grazers, particularly megaherbivores, as main drivers of grazing lawns formation and maintenance, can affect the local climate of African savannas. By creating grazing lawns, herbivores also prevent shrub encroachment and the changes in albedo (and consequently, in local climate) that this process provokes. Another important aspect of this study is to supply more empirical data on the importance of a megaherbivore, such as white rhino, to the ecosystem and the possible consequences of its removal, which in light of the recent poaching crisis might be a reality not so far away.